The noisy way to bed - Whybrow, Ian.; Beeke, Tiphanie (New York : Arthur A. Levine Books, 2004)
As a sleepy boy decides it is bedtime and sets out across the farm toward home, he meets several animals who, in their noisy way, express the same idea.
3.3
K-3
Keywords: Bedtime -- Fiction; Domestic animals -- Fiction; Animal sounds -- Fiction; Bedtime -- Fiction; Domestic animals -- Fiction; Animal sounds -- Fiction